2019
DOI: 10.1507/endocrj.ej18-0348
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric, gene rearrangement, and karyotypic analyses of 110 cases of primary thyroid lymphoma: a single-institutional experience in Japan

Abstract: Ancillary studies for primary nodal lymphomas have been well documented; however, studies of primary thyroid lymphoma (PTL) are limited. Here, we aimed to clarify the clinicopathological, flow cytometric, gene rearrangement, and karyotypic characteristics of PTL by investigation of a large series at a single institute. We performed flow cytometric, IgH rearrangement, and karyotypic analyses of 110 PTL tissues surgically resected at Kuma Hospital between January 2012 and April 2017. All PTLs were of B-cell orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(40 reference statements)
2
14
0
Order By: Relevance
“…Interestingly, of all the PTLs, while DLBCL was the most frequent (71.9%; including DLBCL transformed from low-grade NHL) subtype in western literature, MALT lymphoma was the commonest (41.1%) in Asian studies. Some recent studies have subclassified DLBCL into germinal and post-germinal center type (12,14,18,26). Other rare subtypes of PTL reported include follicular lymphoma (FL), chronic 2).…”
Section: Prevalence and Spectrum/classification Of Ptlmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, of all the PTLs, while DLBCL was the most frequent (71.9%; including DLBCL transformed from low-grade NHL) subtype in western literature, MALT lymphoma was the commonest (41.1%) in Asian studies. Some recent studies have subclassified DLBCL into germinal and post-germinal center type (12,14,18,26). Other rare subtypes of PTL reported include follicular lymphoma (FL), chronic 2).…”
Section: Prevalence and Spectrum/classification Of Ptlmentioning
confidence: 99%
“…A study from Asia compared the cytomorphology of PTL on LBC with that of conventional smears. This study was not included in the analysis in this review because of overlapping study period with another study published from the same institute (14). The authors reported that on LBC large elongated swollen nuclei act as a clue to differentiate PTL from non-neoplastic lymphoid cells and that lymphoglandular bodies are not reliable for diagnosing PTL (49).…”
Section: Fnacmentioning
confidence: 99%
See 3 more Smart Citations